Tandem UGT71B5s Catalyze Lignan Glycosylation in Isatis indigotica With Substrates Promiscuity - Chen, Xiao; Chen, Junfeng; Feng, Jingxian; Wang, Yun; Li, Shunuo; Xiao, Ying; Diao, Yong; Zhang, Lei; Chen, Wansheng (Frontiers in Plant Science, 2021)
Lignans are a class of chemicals formed by the combination of two molecules of phenylpropanoids with promising nutritional and pharmacological activities. Lignans glucosides, which are converted from aglycones catalyzed by UDP glycosyltransferases (UGTs), have abundant bioactivities. In the present study, two UGTs from Isatis indigotica Fort., namely IiUGT71B5a and IiUGT71B5b, were observed to catalyze the glycosylation of lignans with promiscuities toward various sugar acceptors and sugar donors, and pinoresinol was the preferred substrate. IiUGT71B5a was capable of efficiently producing both pinoresinol monoglycoside and diglycoside. However, IiUGT71B5b only produced monoglycoside, and exhibited considerably much lower activity than IiUGT71B5a. Substrate screening indicated ditetrahydrofuran isessential structural characteristic for sugar acceptors. The transcription of IiUGT71B5 genes was highly consistent with the spatial distribution of pinoresinol glycosides, which suggested that IiUGT71B5s may play biological roles in the modification of pinoresinol in I. indigotica roots. This study not only provides insights into lignan biosynthesis, but also helps to elucidate the functional diversity of the UGT family.